CRISPR-Cas Dynamics in Carbapenem-Resistant and Carbapenem-Susceptible Klebsiella pneumoniae Clinical Isolates from a Croatian Tertiary Hospital - Ivana Jurić; Marko Jelić; Manda Markanović; Lucija Kanižaj; Zrinka Bošnjak; Ana Budimir; Tomislav Kuliš; Arjana Tambić-Andrašević; Ivana Ivančić-Baće; Ivana Mareković (Pathogens, 2025)
(1) Background: CRISPR-Cas systems provide adaptive immunity against mobile genetic elements (MGEs) carrying antimicrobial resistance (AMR) genes. Carbapenem-resistant (CR) Klebsiella pneumoniae is a major public health concern, and the role of CRISPR-Cas in its resistance is understudied. This study explored CRISPR-Cas associations with multidrug resistance in clinical K. pneumoniae. (2) Methods: 400 K. pneumoniae isolates (200 CR and 200 carbapenem susceptible (CS)) were analyzed. Carbapenemase genes (blaOXA-48, blaNDM-1, blaKPC-2), cas1, rpoB, and CRISPR1-3 loci were identified by PCR, while only CRISPR loci were sequenced. Genetic relatedness was assessed via PFGE, MLST, and spacer analysis. Statistical analysis utilized chi-squared and Fisher’s exact tests. (3) Results: CRISPR-Cas was present in 15.8% of isolates, mainly subtypes I-E and I-E* (93.3%), with CRISPR3 loci showing the greatest spacer diversity. Clonal complexes ST14/15/101 (CR) and ST35 (CS) were identified. blaOXA-48 was linked to CRISPR-Cas-negative strains, while blaNDM-1 and blaKPC-2 were more frequent in CRISPR-Cas-positive strains (p < 0.0001). Imipenem/relebactam resistance was higher in CRISPR-Cas-negative isolates. (4) Conclusions: K. pneumoniae CRISPR-Cas systems correlate with specific carbapenemase profiles, suggesting pressure against blaOXA-48 acquisition. The coexistence of I-E and I-E* subtypes highlight synergies in targeting MGEs. CRISPR loci could be tools for subtyping organisms following MLST.